Apparent Motion Can Impair and Enhance Target Visibility: The Role of Shape in Predicting and Postdicting Object Continuity - Lenkic, Peter J.; Enns, James T. (Frontiers in Psychology, 2013)
Some previous studies have reported that the visibility of a target in the path of an apparent motion sequence is impaired; other studies have reported that it is facilitated. Here we test whether the relation of shape similarity between the inducing and target stimuli has an influence on visibility. Reasoning from a theoretical framework in which there are both predictive and postdictive influences on shape perception, we report experiments involving three-frame apparent motion sequences. In these experiments, we systematically varied the congruence between target shapes and contextual shapes (preceding and following). Experiment 1 established the baseline visibility of the target, when it was presented in isolation and when it was preceded or followed by a single contextual shape. This set the stage for Experiment 2, where the shape congruence between the target and both contextual shapes was varied orthogonally. The results showed a remarkable degree of synergy between predictive and postdictive influences, allowing a backward-masked shape that was almost invisible when presented in isolation to be discriminated with a d’ of 2 when either of the contextual shapes are congruent. In Experiment 3 participants performed a shape-feature detection task with the same stimuli, with the results indicating that the predictive and postdictive effects were now absent. This finding confirms that shape congruence effects on visibility are specific to shape perception and are not due to either general alerting effects for objects in the path of a motion signal nor to low-level perceptual filling-in.